Homo ritualis: Hindu ritual and its significance for ritual theory - Michaels, Axel (Oxford ritual studies series, 2016)
Machine generated contents note: -- Preface -- Acknowledgements -- Abbreviations -- Plates and Figures -- Pronunciation of Indian Words -- Introduction -- Part I: Framing -- 1. The Beginning of Rituals -- 1.1 The Solemn Intention (samkalpa) -- 1.2 Greeting and Ritualized Greeting (namaskara) -- Conclusion -- Part II: Formality -- 2. Repetitive Rules (vidhi) -- 2.1 The Grammar of Rituals -- 2.2 A Preliminary "Grammar" of Newar Life-cycle Rituals -- 2.3 Rituals in Handbooks (paddhati) -- 3. Agency in Ritual -- 3.1 Ritual Competency (adhikara) -- 3.2 Atonements for Ritual Mishaps (prayascitta) -- 3.3 The Comic Side of Ritual Formality -- 4. Performed and Played Rituals (lila) -- 4.1 Music and Ritual Music -- 4.2 Dance and Ritual Dance -- 4.3 Emotions and Ritual Emotions -- Conclusion -- Part III: Modality -- 5. Individualized and Domestic Rituals (samskara) -- 5.1 The Boy's Initiation -- 5.2 The Girl's Initiation -- 5.3 The Marriage -- 5.4 Death Rituals and Redemption -- 6. Collective and Public Rituals -- 6.1 Temple Festivals (utsava) -- 6.2 Vows (vrata) -- 6.3 Pilgrimages and Processions (yatra) -- 7. Transcendence in Rituals -- 7.1 The Vedic Sacrifice (yajña) -- 7.2 The Fire Sacrifice (homa) -- 7.3 Worship and Prayer (puja) -- 7.4 E-darshan and Cyber-puja -- Conclusion -- Part IV: Meaning -- 8. Meaning and Function -- 8.1 The Cultural Studies Approach -- 8.2 The Cognitive Sciences approach -- 9. The Purvamimamsa Theory of Ritual Efficacy -- Conclusion -- Part V: The Hindu Path of Ritual-Summary -- Appendix: Automatic Detection of Ritual Structures -- Glossary -- References